Pengaruh Atribut, Implementasi CHSE, dan Kualitas Layanan terhadap Kepuasan Pengunjung Agrowisata Taman Edelweiss Karangasem Bali - DIARTA, I KETUT SURYA; SUKENDAR, NI MADE CLASSIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
The Effect of CHSE Implementation on Image, Trust, and Visitor Satisfaction at the Edelweiss Agrotourism Park Karangasem Bali The achievement of visitor satisfaction in tourist destinations will determine their survival in the future. During the Covid-19 Pandemic, the implementation of CHSE (cleanliness, healthy, safety, and environment sustainability) is also seen as very decisive in addition to destination attributes and destination service quality. Therefore, empirical research in the Karangasem’s Edelweiss Agrotourism Park destination is very important to carry out. The study used 100 visitors as respondents. Perceptual categories were analyzed using class intervals, while the effect of exogenous variables on endogenous variables was analyzed using SEMPLS with WarpPLS 3.0 for Windows. The results showed that the visitor's perception of Edelweiss Agrotourism Park as a whole fell in the good category. The destination attribute variable falls in the good category, the CHSE implementation variable falls in the good category, the destination service quality variable falls in the good category, and for visitor satisfaction at the destination falls in the satisfied category. Visitor satisfaction at the Edelweiss Agrotourism Park is significantly influenced by destination attributes and destination service quality. While the implementation of CHSE has no significant effect in shaping visitor satisfaction at the destination. The implication of this research is that managers are obliged to design the implementation of CHSE not to make visitors anxious but to be integrated as a hospitality service while still implementing standard health protocols and having a pleasant atmosphere. In essence, the policy of implementing CHSE at the destination does not make it a burden for potential visitors which is characterized by the negative influence it has in building satisfaction with the destination.